From Sepharad to the World - Rózsavári Nóra (Humán Innovációs Szemle)
Ladino holds a vital place in Sephardic identity and cultural heritage, embodying the legacy of the descendants of Spanish-speaking Jews who were exiled from the Iberian Peninsula in 1492. This language is not simply a linguistic blend; it is a unique fusion of Old Spanish with elements of Hebrew, Arabic, Turkish, Greek, Italian, French, and other languages, reflecting the diverse regions and cultures Sephardic Jews encountered over centuries. Ladino developed and thrived in Sephardic communities across a wide geography, including the Balkans, North Africa, the Eastern Mediterranean, and eventually the Americas, adapting to each locale while retaining its foundational Spanish roots. As a living repository of Sephardic history and values, Ladino has served as a vehicle for storytelling, poetry, music, religious expression, and daily communication, embodying both resilience and continuity. However, as the number of native speakers has diminished, Ladino is now classified as an endangered language. Recognizing its cultural and historical significance, numerous initiatives today are devoted to its preservation and revitalization. Scholars, cultural organizations, and community members are working together to document the language, produce new literature, teach it to younger generations, and promote its use in digital media. These efforts aim to ensure that Ladino continues to be an enduring part of Sephardic culture.